Utilization of Nanosilver as An Antifungal To Commercialize Nanomaterial Preservatives - Taufikurohmah, Titik; Nabila, Awiddah Zuhroh; Dewi, Arfinda Mulya; Puspitasari, Putri Amalia; Safitri, Elys (Chemistry Department, The University of Brawijaya, 2025)
Nanosilver is a silver-based material with a particle size of less than 100 nm. This study aimed to evaluate the antifungal ability of nanosilver used in a preservative in cosmetic and beverage preparations. The synthesis of nanosilver in this study produced particle with a spherical morphology and sizes ranging from 5-46 nm, with an average size of 28.33 nm and demonstrated good stability. Antifungal tests were in this study were carried out on cosmetic and beverage preparations, namely body lotion, serum, lip balm, and mangrove fruit (Sonneratia caseolaris) syrup. In the body lotion, the percentage of fungi in F0, F1, F2, F3, and F4 was 32.6%, 7.8%, 16.6%, 12.8%, and 11.4%, respectively. In serum samples, the percentage of fungial growth in F0, F1, F2, F3, and F4 was 24.6%, 10.6%, 17.4%, 15.6%, and 12.4%. In lip balm samples, the corresponding values were 30.2%, 5%, 22.6%, 18.2%, and 10.8%. In the mangrove fruit syrup sample, the percentages were 29%, 8.6%, 17%, 14.6%, and 12.2%. From these results, nanosilver at the highest percentage (15%), was unable to defeat the antifungal effectiveness of conventional preservatives.